2011
DOI: 10.1007/s00216-010-4640-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of non-covalent interactions of luotonin A derivatives and the DNA minor groove as a first step in the study of their analytical potential as DNA probes

Abstract: The interaction between DNA and several newly synthesized derivatives of the natural anticancer compound luotonin A has been studied. The results from our work reveal an effective and selective alkaloid/double-stranded DNA (ds-DNA) interaction. In the presence of increasing amounts of ds-DNA, a noticeable fluorescence quenching of the luotonin A derivatives under study was observed. However, this effect did not take place when single-stranded DNA (ss-DNA) was employed. The association constant alkaloids/ds-DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In this Article, the binding mechanisms of berberine to DNA was studied by UV–vis absorbance and fluorescence spectroscopy. High sensitivity of the fluorescence spectroscopy makes fluorescence probes valuable tools in chemistry, materials science, biology, and medicine to look into the properties of environment they are associated with. Upon association with biomacromolecules, such as DNA, the emission intensity of the probe increases, and they are useful markers in genomics, as the binding with the host molecule enhances fluorescence emission. In the present study, we demonstrated the intercalative binding mode between BH and DNA; this finding may help to design new efficient probes for the fluorometric detection of DNA, thus replacing many toxic and carcinogenic probes.…”
Section: Introductionmentioning
confidence: 99%
“…In this Article, the binding mechanisms of berberine to DNA was studied by UV–vis absorbance and fluorescence spectroscopy. High sensitivity of the fluorescence spectroscopy makes fluorescence probes valuable tools in chemistry, materials science, biology, and medicine to look into the properties of environment they are associated with. Upon association with biomacromolecules, such as DNA, the emission intensity of the probe increases, and they are useful markers in genomics, as the binding with the host molecule enhances fluorescence emission. In the present study, we demonstrated the intercalative binding mode between BH and DNA; this finding may help to design new efficient probes for the fluorometric detection of DNA, thus replacing many toxic and carcinogenic probes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when plotting the values of the fluorescence intensity ratios versus the quencher concentration, a straight line should be obtained whose ordinate at the origin should be in the vicinity of 1.0. The value of the slope will correspond to the experimental value of the Stern–Volmer constant, which shows the effectiveness of the fluorescence quenching process and allows for the estimation of the magnitude of the sensor–protein interaction [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…The length of the DNA double helix was increased upon binding of the intercalating agents. This elongation of the polymer led to increase in the viscosity of the solution [52] . The interaction between CT DNA and the complexes (1-5) were investigated by viscosity measurements.…”
Section: Table 4: Electrochemical Data Of the Synthesized Complexes (mentioning
confidence: 99%